MODELLING OF CO-AXIAL AND TRI-AXIAL MILLIFLUIDIC DEVICES FOR CO-EXTRUSION OF SEMI-SOLID SOLIDS - Abdo Ali Al-Sharai, Abdo Ali Al-Sharai; Chin Fhong Soon, Chin Fhong Soon; Chan Hwang See, Chan Hwang See; See Khee Yee, See Khee Yee; Kian Sek Tee, Kian Sek Tee; Mohammed Abdul Wahab, Mohammed Abdul Wahab (utm, 2023)
With the use of a milli-fluidics device, it is possible to manipulate small amounts of fluid in the millimeter range with pinpoint accuracy. The millifluidics are currently lacking in studies of the relationship between fluid viscosity, output velocity and output pressure. Thus, this study examines the effects of viscosity on fluid dynamics in the co-axial and tri-axial milli-fluidics. This geometry of the co-axial and tri-axial milli-fluidics consist of single outlet, two inlets and three inlets, respectively. The tri-axial milli-fluidics is 46 mm long and 11.31 mm wide, while, the coaxial milli-fluidic is 64.73 mm long and 9.2 mm wide. The co-axial milli-fluidics constituted of 775 domain elements and 147 boundary elements, while, the tri-axial milli-fluidics mesh constituted of 1518 domain elements and 178 boundary elements. Laminar flow was observed for the flow of the materials through the channels. When the dynamic viscosity approaches 5 mPa.s, the simulation reveals that the flow rate is inversely proportional to the dynamic viscosity for co-axial millifluidics. It was difficult to combine fluids with different viscosities with small volume of water in a narrow boundary, thus the parallel flow of material was observed. When using the one outlet channel for the tri-axial milli-fluidics, the assemble pressure at the three inlets was decreased compared with coaxial milli-fluidic. Even when the dynamic velocity of the fluid at outlet 1 increased, its velocity remained consistent. An extruder using tri-axial millifluidics can be used if the interfacial tension for intake 1 is higher than for inlet 2 and the dynamic viscosity of fluid 1 is above 2 mPas, according to the volumetric fraction model. The tri-axial milli-fluidic was found to be suitable for producing cladding of material with the balanced pressure from the two side channels.